2014
DOI: 10.3906/biy-1310-69
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of enterocin KP in combination with sublethal factors on Escherichia coli O157:H7 or Salmonella Typhimurium in BHI broth and UHT milk

Abstract: The effects of physical and chemical sublethal treatments on the antibacterial activity of enterocin KP produced by Enterococcus faecalis KP against Escherichia coli O157:H7 and Salmonella Typhimurium were investigated. Enterocin KP was not active against intact cells of E. coli O157:H7 or S. Typhimurium. However, the use of enterocin KP together with ethylenediaminetetraacetic acid (50 mM), sodium tripolyphosphate (50 mM), sublethal heating (60 °C for 10 min), cold shock (-20 °C for 2 h), or acid stress (mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Several authors have reported the difficulty of inhibition of gram-negative bacteria by bacteriocins; AHMADOVA et al (2013) and ACUÑA and BARROS-VELÁZQUEZ (2015) did not observe an inhibitory effect by purified enterocins against strains of E. coli and Salmonella. ALAKOMI et al (2003) and YILDIRIM et al (2014) reported the antagonistic action of the enterocin KP against E. coli O157:H7 and Salmonella only when the enterocins were combined with EDTA or sodium tripolyphosphate. These reports differ from the results obtained in this study, where the action of the enterocin MF5 on STEC was observed without the addition of an ion chelator.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported the difficulty of inhibition of gram-negative bacteria by bacteriocins; AHMADOVA et al (2013) and ACUÑA and BARROS-VELÁZQUEZ (2015) did not observe an inhibitory effect by purified enterocins against strains of E. coli and Salmonella. ALAKOMI et al (2003) and YILDIRIM et al (2014) reported the antagonistic action of the enterocin KP against E. coli O157:H7 and Salmonella only when the enterocins were combined with EDTA or sodium tripolyphosphate. These reports differ from the results obtained in this study, where the action of the enterocin MF5 on STEC was observed without the addition of an ion chelator.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that most bacteriocins inhibit Gram-positive bacteria, while the outer lipopolysaccharide membrane of Gram-negative bacteria acts as natural barrier against the entry of bacteriocins into the cell ( Gyawali and Ibrahim, 2014 ; Yildirim et al, 2014 ). However, in our study, the CFS obtained from E. faecalis KT11 exhibited antimicrobial activity against 16 of the 30 indicator bacteria, including Gram-negative bacteria, with inhibition zones ranging from 14 to 20 mm ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, it has been previously reported that enterocins remain completely stable after treatment with organic solvents ( Isleroglu et al, 2011 ; Perumal and Vankatesen, 2017 ). The stability of bacteriocins after treatment with solvents proves that bacteriocins do not have lipid moieties ( Yildirim et al, 2014 ). This finding is also important because many organic solvents are used in bacteriocin purification from supernatants ( Aspri et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to their external membrane consisting of extensive amounts of protein, phospholipids and polysaccharide may act as a barrier to the action of nisin on the cytoplasmic membrane [ 38 , 39 ]. Yildirim et al [ 40 ] explained that enterocin KP alone did not act against intact cells of Salm. Typhimurium and E. coli but in the presence of physio-chemical sublethal treatments decreases their cell number.…”
Section: Discussionmentioning
confidence: 99%